Simulation of Factor on SOC Inconsistency within a Series‐Connected Lithium‐Ion Battery Pack. Issue 12 (13th September 2022) - Zhang, Yanqin; Yang, Ran; Chi, Rongchen
Abstract: This paper outlines a new simulation approach to study the effect of factors on the state of charge (SOC) consistency of Li‐ion battery packs. The proposed method is based on a system model and the Monte Carlo method. The system model includes 100 serial connected equivalent circuit models and their respective parameters. This paper divides the internal and external factors into two categories: independent factors such as internal resistance, capacity, Coulombic efficiency, leakage current, and comprehensive factors related to temperature. The Monte Carlo method simulates the differences and distribution of independent factors among cells. Temperature‐dependent factors are modeled with empirical formulas. Simulation results show that the main factors affecting SOC consistency are differences in battery temperature, leakage current, and Coulombic efficiency. Meanwhile, slight differences in capacity and internal resistance have little effect on SOC inconsistency. Furthermore, this paper demonstrates the effectiveness of the system model. Abstract : A simulative approach is proposed to study the influence of factors on state of charge consistency in battery packs. The method is based on a system model which includes 100 serial connected equivalent circuit models and their factor models. The simulation results can shed light on the factors that battery management should focus on.